ANALISIS KONTRASTIF UNGKAPAN MENGINGATKAN SESUATU DALAM PERCAKAPAN BAHASA INDONESIA DAN BAHASA JEPANG: SEBUAH TINJAUAN SOSIOLINGUISTIK - Sonda Sanjaya; Thamita Islami Indraswari (IZUMI, 2015)
This research is aimed to investigate type of utterance and communicating style between Japanese and Indonesian in reminding something. The difference between two language may hindrance communicating process, and lead to misconception. Thus the researchers conclude that further study in this topic is essential. Sample was taken from 24 participants, which is required to conversate according to condition given in roleplay card. Participants are acquintances, divided to act as the borrower and as the giver. The giver had promised to lend the borrower something, and the borrower supposed to remind the giver about it. The data shows that in Indoneisan, it is common for the borrower to take initiative when reminding something or taking the promised thing. It is also found that the giver often asked to be reminded again by the borrower in means of texting or phonecall. Meanwhile, in Japanese the act is reversed. The giver is taking an initiative, and even offers to bring the promised thing. Although the borrower is also taking an initiative, it is not common for the giver to asked to be reminded again by the borrower.